Fuel Flow Rate and Rotational Speed Analysis on the Plug-In Hybrid Electric Vehicle Using Hybrid Control System Module Modification Combination Management - Arif Wahyudiono; Faruq Avero Azhar; Azamataufiq Budiprasojo; Yuana Susmiati (P3M Politeknik Negeri Jember, 2026)
This study investigates the fuel flow rate and engine rotational speed characteristics of a plug-in hybrid electric motorcycle using a Hybrid Control System Module Modification Combination Management (HCS-MCM) framework. The proposed system is designed for conversion-based applications at the workshop level, addressing the gap between advanced hybrid control strategies and practical implementation. A parallel hybrid configuration was adopted, integrating an internal combustion engine (ICE) and a 3 kW electric motor with a gear-dependent control strategy. Experimental testing was conducted under first and second gear conditions by analyzing the relationship between vehicle speed, engine speed (RPM), and the time required to consume 5 ml of fuel. The results show that the hybrid system consistently produces longer fuel consumption times compared to the conventional system, indicating improved fuel efficiency. The most significant improvement occurs in first gear, where the electric motor provides dominant torque assistance at low speeds, reducing the load on the ICE. In second gear, the hybrid system still demonstrates better efficiency; however, the performance gap decreases as the ICE becomes more dominant at higher speeds. These findings confirm that the proposed HCS-MCM framework effectively enhances fuel efficiency, acceleration performance, and energy utilization. The study contributes to the development of practical hybrid control systems for motorcycle conversion, particularly for small-scale workshop applications in developing countries.